Nanoscopic Visualization of Cross‐Linking Density in Polymer Networks with Diarylethene Photoswitches. Issue 38 (23rd August 2018) - Siemes, Eric; Nevskyi, Oleksii; Sysoiev, Dmytro; Turnhoff, Sarah K.; Oppermann, Alex; Huhn, Thomas; Richtering, Walter; Wöll, Dominik
Abstract: The in situ nanoscopic imaging of soft matter polymer structures is of importance to gain knowledge of the relationship between structure, properties, and functionality on the nanoscopic scale. Cross‐linking of polymer chains effects the viscoelastic properties of gels. The correlation of mechanical properties with the distribution and amount of cross‐linkers is relevant for applications and for a detailed understanding of polymers on the molecular scale. We introduce a super‐resolution fluorescence‐microscopy‐based method for visualizing and quantifying cross‐linker points in polymer systems. A novel diarylethene‐based photoswitch with a highly fluorescent closed and a non‐fluorescent open form is used as a photoswitchable cross‐linker in a polymer network. As an example for its capability to nanoscopically visualize cross‐linking, we investigate pNIPAM microgels as a system known with variations in internal cross‐linking density. Abstract : Nanoscopy on polymer cross‐links : A cross‐linking photoswitch allows the visualization of cross‐linker positions with super‐resolution fluorescence microscopy giving unprecedented insights into the heterogeneity of polymer networks which are essential for a fundamental understanding and application of cross‐linked polymer structures.